Distribution and habitat use of the Bluenose caribou herd in mid-winter - Carruthers, D. R.; Ferguson, S. H.; Jakimchuk, R. D.; Sopuck, L. G. (Rangifer, 1986)
The mid-winter distribution and densities of the Bluenose caribou herd were compared with previous surveys over six years and were similar in all years except 1981 when exceptionally mild weather prevailed. Differences in group size, distribution and habitat use between sexes were noted in 1983. Caribou were distributed disproportionately to availability of vegetation types and used lakes significantly more than expected based on their occurrence. Male groups used conifer cover more than did female-calf groups which used open areas (lakes, fens, bogs) more than males. Cow-calf groups chose areas with a higher small lake density compared to lake density generally available. Generally caribou preferred habitat between 200 and 300 m in elevation with high densities of lakes less than 1 km2 in size. Snow depths and hardness were greater in most unoccupied habitats than in occupied habitats. Wolves were associated with high densities of cow/calf groups.